EXPERIENCE OF SEA WATER HYPERTONIC SOLUTION APPLICATION FOR TOPICAL TREATMENT OF CHRONIC TONSILLITIS - E.P. Karpova; E.F. Fayzullaev ("Paediatrician" Publishers LLC, 2006)
The study examined the effectiveness of sea water hypertonic solution (Aqua Maris troath and oral cavity spray, Jadran, Croatia) medication to treat chronic tonsillitis of the compensated form on 84 children aged between 5 and 15. All children had their tonsil lacunae rinsed in a day № 6-8. 64 children had them rinsed with the sea water hypertonic solution (main group), while 20 children had them rinsed with the nitrofural solution (comparison group). Treatment effectiveness was determined according to dynamics of main symptoms (odynophagia, dysphagia, hyperemia and mucosa infiltration of pillars of the fauces), as well as the degree of tonsil bacterial number before and after treatment (by the 14th day). The dynamic analysis of subjective data during treatment revealed more significant and positive changes among the children of the main group if compared with patients from the comparison group. After treatment the researchers noticed reduction of tonsil bacterial number among 90,62% of children from the main group, whereas this rate made up 60% in the comparison group. Acquired data allowed recommending this medication for the multimodality therapy of infant adenoid disease. Key words: chronic tonsillitis, treatment, children, sea water hypertonic solution.